EKSPRESI KEMARAHAN YANG DIGUNAKAN OLEH PARA TOKOH DALAM SERIAL CHRONICLES OF NARNIA 1 - Endar Septian Kusumawardhani; Sigit Haryanto; Titis Setyabudi (ELTIN Journal, 2024)
The aims of this study are to investigate the pragmalinguistic forms of anger and to describe the intentions of the anger expressions shown by the characters in the Narnia 1 movie. This research is qualitative research. The data from this study are all conversations that express anger in the Narnia Series 1. In collecting data, researchers used the documentation method. The data were analyzed using Madow's theory of pragmalinguistic forms of anger expressive and Leech's theory of speaking situations. The results of this study indicate that there are three pragmalinguistic forms of angry expressions used by the characters. The forms of the anger expressive are the direct form (26), the vague form (12), and the indirect form (1). The results of this study also show that there are eleven meanings of angry expressions. They are questioning (5), asserting (11), commanding (5), criticizing (2), mocking (5), disbelieving (2), ordering (1), suggesting (1), disagreeing (2), warning (3), and declaring (2). Thus, it can be concluded that direct form of anger is the form that appears the most in Narnia movie and asserting is the most dominant intention used by the characters in Narnia movie